Correlational Study of Language Learning Attitude and Speaking In Indonesian Context (Case Study) - Syafrizal Syafrizal; Sutrisno Sadji Evenddy; Nurhaedah Gailea; Tina Nurzachra Latifah Riski Liana (English Department - University of Sultan Ageng Tirtayasa, 2018)
The important role of attitude in language learning toward English has been increasingly recognized in developing teaching learning English especially in Speaking. However, only a few studies on the correlation between attitude in language learning and speaking. This study aimed at investigating whether there is a correlation between students’ language learning attitude toward English and students’ Speaking in Indonesian Senior High School. The research sample consisted of 80 Indonesian students of class XI-AP 1 until XI-AP 3 in the academic year 2016/2017. The research employs ex-post facto design. The data collected through questionnaire and documentation was analyzed by using Pearson Product Moment Correlation. It shows that there is a strong correlation between dependent and independent variables. The correlation value of the calculation is 0,776 it means the correlation is at strong grade. Based on the correlation value, it can be found the coefficient determination is 60%, it implies that students’ language learning attitude toward English and Speaking Achievement have strong correlation. It can be implied that students’ language learning toward English and Speaking Achievement has significant positive correlation at strong grade. It is show that if students have positive language learning toward English the result of their speaking will be good too. The other 40% is not to be discussing in this research.